Course of subthreshold depression into a depressive disorder and its risk factors - Tuithof, Marlous; ten Have, Margreet; van Dorsselaer, Saskia; Kleinjan, Marloes; Beekman, Aartjan; de Graaf, Ron (Journal of affective disorders, 2018)
•Adults with subthreshold depression were worse off on nearly all examined characteristics (i.e. vulnerability, psychopathology, physical health, functioning) and 3-year course than the asymptomatic group, whereas they were better off than the depressive disorder group.•As only 12% of the subthreshold depression cases developed a depressive disorder over three years, subthreshold depression appears not, by itself, to carry a sufficient a priori risk to warrant focusing indicated prevention on all individuals with subthreshold depression.•The risk indicators for a depressive disorder that were uncovered among subthreshold cases could help to further focus indicated interventions, for example at those with physical comorbidity. Information on the natural course of subthreshold depression and risk factors for the development of a full-blown depressive disorder in the general population is scarce. This information is crucial to understand the development of depression and to advance indicated depression prevention. Using longitudinal data from a representative population-based study (the Netherlands Mental Health Survey and Incidence Study-2) we assessed 3-year course of subthreshold depression (depressive symptoms causing clinically significant distress for at least 2 weeks, or for 3 days per month for a year; n = 120), compared to an asymptomatic group (n = 4111) and a depressive disorder group (major depression or dysthymia; n = 294). Next, risk factors for the development of a depressive disorder among adults with subthreshold depression were determined. Twelve percent of the subthreshold cases developed a full-blown depressive disorder during 3-year follow-up. Risk factors were lower social support, having recurrent short episodes of depressive symptomatology, remitted and current anxiety disorder, remitted substance use disorder, lifetime suicide thoughts, a chronic physical disorder and diminished mental and physical functioning. The number of subjects with subthreshold depression that developed a depressive disorder was small. This limits the possibility to detect significant risk factors. Only a minority of the subthreshold cases developed a full-blown depressive disorder over three years. This shows that subthreshold depression does not, by itself, carry an a priori risk to warrant focusing indicated prevention. The identified risk factors could help to detect those subthreshold cases in whom depression prevention is economically and practically viable.